Bridging Learning and Practice: Exploring Transfer and Learning in Finance Internships - Andersen, Michael Wædeled; Nielsen, Sara Møller; Sørensen, Marlene Højmark (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This paper explores how transfer and learning unfolds for students in professional bachelor’s programmes during internships in a financial context. Reflective Practice-based Learning (RPL), which emphasises the interplay of experience, thinking, and action, is particularly relevant in a practice-oriented education, where students must bridge theoretical knowledge and professional practice. Internships serve as key moments, offering students the opportunity to apply their academic learning in real-world contexts. However, transfer – the process of applying knowledge and competencies in new settings – does not occur automatically. It requires supportive conditions such as reflection, feedback, and opportunities for professional engagement. This study is guided by theoretical perspectives on learning and transfer, particularly drawing on Illeris’ learning dimensions, Mezirow’s theory of transformative learning, and Wahlgren’s perspectives on transfer conditions. While transfer has been widely studied in fields such as teaching and healthcare, the financial sector remains underexplored. This sector is shaped by distinct features, including complex regulatory constraints, varying degrees of student preparedness, and evolving professional expectations. This study investigates how students experience transfer during their internship, and how different conditions influence this process. Through qualitative data from semi-structured focus group interviews conducted across three phases of the internship period, this study contributes to the ongoing exploration of RPL in an internship context. The study contributes to understanding reflective and transferable learning in the financial sector by highlighting the role of motivation, psychological safety, and structured reflection. It underscores the need for intentional internship design in contexts where access and learning opportunities are not guaranteed.